Pengaruh Customer Relationship Management dan Kualitas Pelayanan terhadap Loyalitas Konsumen : (Studi pada Konsumen Rena Fashion & Beauty) di Tuban - Farichatun Nisa’; Nadhila Bonazier G; Damayanti Eka W; Yaremia F.M Saragih (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
This research focuses on the impact of Customer Relationship Management and Service Quality on Consumer Loyalty at Rena Fashion & Beauty, Tuban. This research identifies the following problems: 1) The influence of Customer Relationship Management on consumer loyalty at Rena Fashion & Beauty, Tuban; 2) The impact of service quality on consumer loyalty at Rena Fashion & Beauty, Tuban; 3) The joint influence of Customer Relationship Management and Service Quality on consumer loyalty at Rena Fashion & Beauty, Tuban. The aim of this research is to assess: 1) The influence of customer relationship management on consumer loyalty at Rena Fashion & Beauty, Tuban; 2) The impact of service quality on consumer loyalty at Rena Fashion & Beauty, Tuban; 3) The joint influence of Customer Relationship Management and Service Quality on consumer loyalty at Rena Fashion & Beauty, Tuban. This research used a survey method with a quantitative approach and involved 95 respondents. Quantitative data analysis was obtained through questionnaires. The research results show that Customer Relationship Management and Service Quality have a positive and significant influence of 49% on consumer loyalty at Rena Fashion & Beauty, Tuban, while the remaining 51% is influenced by other factors. Therefore, it is important for Rena Fashion & Beauty to continue to pay attention to Customer Relationship Management and Service Quality in order to increase their customer loyalty.